Autoxidation of ascorbate mediates lysine N-pyrrolation. (2nd December 2022) - Yoshitake, Jun; Shibata, Takahiro; Chikazawa, Miho; Uchida, Koji
Abstract: Protein N -pyrrolation, which converts lysine residues to N ε -pyrrole-l -lysine (pyrK), is a naturally occurring covalent modification. The pyrrolated proteins have a unique property of binding to DNA-staining agents, such as SYBR Green I (SG), and anti-DNA antibodies, suggesting a physiologically relevant modification that gives rise to DNA mimic protein. These properties of pyrrolated protein are suggested to be associated with innate and autoimmune responses. Short-chain aldehydes derived from lipid peroxidation are thought to be involved in the formation of pyrK. We now report that similar lysine N -pyrrolation also occurs during the metal-catalyzed oxidation of proteins with ascorbate. When human serum albumin (HSA) was incubated with Fe 2+ /ascorbate in the presence and absence of docosahexaenoic acid, the protein was converted to SG-binding proteins even without the polyunsaturated fatty acid. The formation of SG-binding proteins by Fe 2+ /ascorbate was accompanied by the formation of pyrK, which was also detected in ascorbate-treated hemoglobin. Moreover, the metal-catalyzed oxidation of ascorbate produced the pyrrolation factors, glycolaldehyde and glyoxal. These results and the observations that sera from autoimmune-prone MRL- lpr mice recognized modified proteins with Fe 2+ /ascorbate and with glycolaldehyde/glyoxal suggest that the autoxidation of ascorbate, as well as lipid peroxidation, can be a source of autoantigenic N -pyrrolated proteins. Our findings revealed a possible function of ascorbate as an endogenous source of pyrrolated proteins and suggested that the pyrK residues generated in proteins may play a role in the innate and autoimmune responses associated with the oxidative metabolism of ascorbate.